2018
DOI: 10.1136/bmjopen-2017-020450
|View full text |Cite
|
Sign up to set email alerts
|

A UK clinical audit addressing the quality of prescribing of sodium valproate for bipolar disorder in women of childbearing age

Abstract: ObjectivesTo review prescribing practice concerning valproate, an established human teratogen, for the management of bipolar disorder in women of childbearing age.DesignThe Prescribing Observatory for Mental Health conducted a baseline clinical audit in the UK, as part of a quality improvement programme.ParticipantsSix hundred and forty-eight clinical teams from 55 mental health Trusts submitted retrospective treatment data relating to patients with a diagnosis of bipolar disorder.ResultsOf the audit sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 14 publications
2
27
0
2
Order By: Relevance
“…A similar study on the population of Stockholm found no influence of the intervention for girls and women being initiated on valproate except the group aged under 45 and diagnosed with psychiatric disorders [18]. While sporadic study results are contrasting and often consist of prevalent use comparison, the strengthened warning by EMA in 2014 was overridden by a stricter regulation in 2018 after a new review process, thus indicating possibly insufficient prior action to reduce valproate prescriptions in European health systems [17][18][19]23,33].…”
Section: The Effects Of the 2013-2014 Ema Proceduresmentioning
confidence: 93%
“…A similar study on the population of Stockholm found no influence of the intervention for girls and women being initiated on valproate except the group aged under 45 and diagnosed with psychiatric disorders [18]. While sporadic study results are contrasting and often consist of prevalent use comparison, the strengthened warning by EMA in 2014 was overridden by a stricter regulation in 2018 after a new review process, thus indicating possibly insufficient prior action to reduce valproate prescriptions in European health systems [17][18][19]23,33].…”
Section: The Effects Of the 2013-2014 Ema Proceduresmentioning
confidence: 93%
“…Secondly, it is one of the most cost-effective acne treatments used by patients from different age groups including women of childbearing age (Algoblan et al, 2019;Bérard et al, 2007;Honein et al, 2004). By contrast, it was observed that there were fewer publications on medications prescribed under more recent risk management programmes such as thalidomide, lenalidomide, and valproic acid (Atturu & Odelola, 2015;Brandenburg et al, 2017;Castaneda et al, 2008;Chave et al, 2001;Gotlib et al, 2016;Mulryan et al, 2018;Paton et al, 2018), indicating a need for further investigation of the safety of these medications in terms of adherence to risk management measures for such medications. Good practice guidance suggests that ensuring safe use of medications can have a number of positive effects on treatment outcomes.…”
Section: Risk Managementmentioning
confidence: 99%
“…One factor could be the data sources used by the different studies. Some studies relied on medical records as their source of data (Atturu & Odelola, 2015;Bhakta et al, 2015;Cheetham et al, 2006;Crijns et al, 2012;Force et al, 2012;Fritsche et al, 2011;Gotlib et al, 2016;Hayward et al, 2016;James et al, 2007;Langan et al, 2013;Martin et al, 2008;Mody, Farala, et al, 2015;Mulryan et al, 2018;Paton et al, 2018;Pinheiro et al, 2013;Raguideau et al, 2015;Ruiter et al, 2012;E. B. Schwarz et al, 2010;E.…”
Section: Risk Managementmentioning
confidence: 99%
“…It even returned to black triangle status so that intensive monitoring could be carried out. This monitoring led to the banning of prescribing valproate in women and girls of child bearing age unless a pregnancy prevention programme is in place in early 2018 after the publication of findings and of audits took place (Paton, Cookson, Ferrier, Bhatti, Fagan and Barnes 2018).…”
Section: Prescribing In the Woman Of Childbearing Agementioning
confidence: 99%